Antithrombotic drugs and non-variceal bleeding outcomes and risk scoring systems: comparison of Glasgow Blatchford, Rockall and Charlson scores. Issue 4 (8th June 2016) - Taha, Ali S; McCloskey, Caroline; Craigen, Theresa; Angerson, Wilson J
Abstract : Objectives: Antithrombotic drugs (ATDs) cause non-variceal upper gastrointestinal bleeding (NVUGIB). Risk scoring systems have not been validated in ATD users. We compared Blatchford, Rockall and Charlson scores in predicting outcomes of NVUGIB in ATD users and controls. Methods: A total of 2071 patients with NVUGIB were grouped into ATD users (n=851) and controls (n=1220) in a single-centre retrospective analysis. Outcomes included duration of hospital admission, the need for blood transfusion, rebleeding requiring surgery and 30-day mortality. Results: Duration of admission correlated with all scores in controls, but correlations were significantly weaker in ATD users. Rank correlation coefficients in control versus ATD: 0.45 vs 0.20 for Blatchford; 0.48 vs 0.32 for Rockall and 0.42 vs 0.26 for Charlson (all p<0.001). The need for transfusion was best predicted by Blatchford (p<0.001 vs Rockall and Charlson in both ATD users and controls), but all scores performed less well in ATD users. Area under the receiver operation characteristic curve (AUC) in control versus ATD: 0.90 vs 0.85 for Blatchford; 0.77 vs 0.61 for Rockall and 0.69 vs 0.56 for Charlson (all p<0.005). In predicting surgery, Rockall performed best; while mortality was best predicted by Charlson with lower AUCs in ATD patients than controls (p<0.05). Stratification showed the scores' performance to be age-dependent. Conclusions: Blatchford score was the strongest predictor of transfusion, Rockall's had the strongest correlation with duration of admission and with rebleeding requiring surgery and Charlson was best in predicting 30-day mortality. Modifications of these systems should be explored to improve their efficiency in ATD users.